Recognizing Green Skills Through Non-formal Learning A Comparative Study in Asia - Pavlova, Margarita; Singh, Madhu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This open access book looks into the roles and practices of small and micro-enterprises in formal and informal economies across seven countries and one territory in terms of how they contribute to environmental and sustainable development and green skills promotion. By taking into account the perspectives in these four sectors, catering, automotive, waste management and polyvinyl chloride production, this book maps environmental green practices in the region, identifying mechanisms used to assess existing skills (i.e. knowledge, skills and competencies), and evaluating the potential for green skills inclusion in recognition, validation and accreditation.
Part 1 Debate on the need for green Skills inclusion in the recognition, validation and accreditation (RVA) framework -- Chapter 1 Introduction: Unpacking greening and skills recognition in micro, small and medium enterprises -- Chapter 2 Overview of the regional practices and challenges on environmental protection in four industries -- Chapter 3 RVA in Asia and the Pacific region -- Part 2 Case studies from Asia: Environmentally friendly practices and RVA applications -- Chapter 4 Case study: Bangladesh. The demand side of environmental sustainability through skills recognition -- Chapter 5 Case study: People$1 (Bs Republic of China. Utilising workers$1 (Bskills for improving green competitiveness to address the challenges of greening of industries -- Chapter 6 Case study: Hong Kong Special Administrative Region, People$1 (Bs Republic of China. Realities of MSME: What green skills are included in the RVAs? -- Chapter 7 Case study: India. The role of the Skill Council for Green Jobs (SCGJ) in recognizinggreen skills and upskilling workers in micro, small and medium enterprises -- Chapter 8 Case study: Kazakhstan. Educational challenges in transitioning to a green economy -- Chapter 9 Case study: Malaysia. Recognising green skills in non-formal learning settings -- Chapter 10 Case study: Nepal. The inclusion of green competences in the recognition of prior learning -- Chapter 11 Case study: Philippines. Recognising green skills for environmental and sustainable development in four selected industries -- Part 3 Identifying patterns and building blocks in green skills inclusion in RVA -- Chapter 12 Increasing awareness: Good Practices to Promote Skills Recognition Among Micro, Small and Medium enterprises -- Chapter 13 Recommendations for supporting green skills inclusion in RVA.s
Keywords: Professional education; Vocational education; Education; Professional and Vocational Education; Education; Education